PENGARUH PENGGUNAAN QRIS DAN LITERASI KEUANGAN TERHADAP PERTUMBUHAN UMKM KULINER DI KOTA MALANG - Salsabila Nur Husnia; Wahyu Hidayat Riyanto (Journal of Financial Economics & Investment, 2026)
The financial performance of culinary MSMEs faces challenges in financial management and adaptation to digital payment systems. This study aims to analyze the effect of Quick Response Code Indonesian Standard (QRIS) usage and financial literacy on the growth of culinary MSMEs in Dau District, Malang Regency. The sample consists of MSME actors selected using accidental sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that QRIS implementation and financial literacy have a positive and significant effect on MSME growth. Financial literacy is the most dominant variable. These findings confirm that financial management skills and the use of QRIS help MSMEs increase sales, speed up transactions, and support sustainable business growth. Regional governments are expected to expand financial literacy and digitalization training for MSMEs.